2020
DOI: 10.1159/000506618
|View full text |Cite
|
Sign up to set email alerts
|

The rs11187533 C&#x3e;T Variant of the <b><i>FFAR4</i></b> Gene Is Associated with Lower Levels of Fasting Glucose and Decreases in Markers of Liver Injury in Children with Obesity

Abstract: Introduction: Genetic factors can modulate the development of associated comorbidities in obesity. It has been shown that loss-of-function variants of the free fatty acid receptor 4 (FFAR4) gene negatively affect obesity comorbidities such as insulin resistance and fatty liver disease. Objective: To test the relationships of metabolic factors in children with obesity with variants of the FFAR4 gene. Methods: We performed an association study of 3 single nucleotide polymorphisms (SNPs) of FFAR4 (rs10882273 T>C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…We previously found that the C/T‐T/T genotypes in the rs11187533 SNP were associated with lower levels of fasting glucose and markers of liver injury, suggesting a protective role of the minor T allele (11). In the present study, we show that the C/T‐T/T genotypes have significantly higher expression of FFAR4 than the C/C genotype, linking the expression values to the rs11187533 SNP genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found that the C/T‐T/T genotypes in the rs11187533 SNP were associated with lower levels of fasting glucose and markers of liver injury, suggesting a protective role of the minor T allele (11). In the present study, we show that the C/T‐T/T genotypes have significantly higher expression of FFAR4 than the C/C genotype, linking the expression values to the rs11187533 SNP genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by our group have found significant associations between the FFAR4 rs11187533 single nucleotide polymorphism (SNP) located in intron 2 and several obesity comorbidity parameters (11). Specifically, the mutated C/T‐T/T genotypes were associated with lower values of blood glucose, alanine transaminase (ALT) and gamma‐glutamyl transpeptidase (GGT), which suggests a protective effect of the minor T allele.…”
mentioning
confidence: 99%